PENGARUH MASYARAKAT EKONOMI ASEAN TERHADAP KEBIJAKAN INDUSTRI MANUFAKTUR INDONESIA - IBRAHIM, NOFANSYAH ([Yogyakarta] : Universitas Gadjah Mada, 2015)
This research aims to explain about the influence of ASEAN Economic Community (AEC) 2015 toward Indonesia Manufacturing Policy. Trough theoritical view, AEC as the form of economic integration has two impacts which are good and bad for the country joined AEC. From the good impact, AEC serves large market access and zero tarriff. In the other side, bad impact of AEC makes a country to be market of the other contry’sproduct if they less in competitiveness. Bladwin and Wyploz argue that economic integration influence the country to increase their competitiveness trough theree ways called pro-competitive effects; technological upgrading, budgeting industry, and export orientatation. The ways to incerase the competitiveness contact with the government policy. Government plays significant role trough their policy-pro to competitiveness. This research conclude that AEC gives some influences to government policy of Indonesia manufacturing industries trough the policy of technological upgrading, funding the industries, and increasing export.